WPF 4.5 programming LiveLessons - Rainwater, Jason; Safari eBooks ([S.l.] : Live Lessons, 2014)
"In WPF 4.5 Programming LiveLessons, Jason Rainwater shows how to create rich, next-generation applications with WPF using Visual Studio 2013. Master panels, content and item controls, code behind, binding, resources, styles, templates, behaviors, animations, custom controls, localization, navigation, MVVM, and more! New features on 4.5 are covered, including binding to static properties, automatically updating the source of a data binding via delay, and enabling smooth scrolling with ScrollUnit on VirtualizingStackPanel."--Resource description page.
Title from title screen (viewed July 2, 2014).
Presenter, Jason Rainwater.
Keywords: Windows presentation foundation; Application software; Application software -- Development; Electronic books